2013
DOI: 10.1016/j.molcel.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination of NLRP3 by BRCC3 Critically Regulates Inflammasome Activity

Abstract: NLRP3 is an important pattern recognition receptor involved in mediating inflammasome activation in response to viral and bacterial infections as well as various proinflammatory stimuli associated with tissue damage or malfunction. Upon activation, NLRP3 assembles a multimeric inflammasome complex comprising the adaptor ASC and the effector pro-caspase-1 to mediate the activation of caspase-1. Although NLRP3 expression is induced by the NF-κB pathway, the posttranscriptional molecular mechanism controlling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
508
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(552 citation statements)
references
References 18 publications
20
508
0
9
Order By: Relevance
“…L'étape d'activation de l'inflammasome repose aussi sur des modifications post-traductionnelles de NLRP3. L'assemblage de l'inflammasome nécessite en effet la déubiquitination de NLRP3 par la déubiquitinase BRCC3 (BRCA1/BRCA2-containing complex subunit 3) en aval de tous les activateurs qui ont été testés [38]. Cette déubiquitination semble donc constituer un élément clé de l'activation de l'inflammasome.…”
Section: Les Voies De Signalisation Qui Contrôlent L'assemblage De L'unclassified
See 1 more Smart Citation
“…L'étape d'activation de l'inflammasome repose aussi sur des modifications post-traductionnelles de NLRP3. L'assemblage de l'inflammasome nécessite en effet la déubiquitination de NLRP3 par la déubiquitinase BRCC3 (BRCA1/BRCA2-containing complex subunit 3) en aval de tous les activateurs qui ont été testés [38]. Cette déubiquitination semble donc constituer un élément clé de l'activation de l'inflammasome.…”
Section: Les Voies De Signalisation Qui Contrôlent L'assemblage De L'unclassified
“…Elle repose donc sur des voies de signalisation différentes [20]. Les domaines NACHT et LRR peuvent être ubiquitinés, et NLRP3 présente un mélange de chaînes d'ubiquitines de type K48 et K63 [38]. BRCC3, spécifique des chaînes K63, cible le l'ouverture de pores via le récepteur P2X7 (purinergic receptor P2X 7) [24].…”
Section: Les Voies De Signalisation Qui Contrôlent L'assemblage De L'unclassified
“…It has recently been shown that the DUB BRCC3 profoundly promotes inflammasome activation by deubiquitinating NLRP3, whereas the level of BRCC3 does not correlate with the abundance of NLRP3 after LPS exposure, hinting that non-degradative K63-linked ubiquitination might obstruct NLRP3 inflammasome activation in resting macrophages. 30 The ubiquitin system is also implicated in modulating other subunits of the NLRP3 inflammasome. The ASC can be linearly ubiquitinated by LUBAC, which enhances activation of the NLRP3 inflammasome independent of its positive role in NF-κB signaling.…”
Section: Inflammasome Signalingmentioning
confidence: 99%
“…Le premier signal, résultant souvent de l'engagement d'un récepteur Toll-like, induit une pré-activation de NLRP3 via une modification post-traductionnelle (déubiquitination) [14], une augmentation de la transcription du gène correspondant, ainsi que la transcription du gène codant pour la pro-IL-1. Le second signal est donné par de nombreux activateurs (Tableau I).…”
Section: L'activation De Nlrp3unclassified